PENGARUH MEDIA QUESTION CARD TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS V UPT SD NEGERI 101906 PAGAR JATI - Enjelika Sinaga; Lisbet Novianti Sihombing; Hetdy Sitio (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of Question Card media on Student Learning Outcomes in the Science Subject of Class V of UPT SD Negeri 101906 Pagar Jati. This study uses a quantitative research method with "Pre-Experimental Design" in the form of One Group Pre-test Posttest which was carried out at UPT SD Negeri 101906 Pagar Jati on class V students with a population of 29 people and a sample of 29 people. The data collection technique for this study used 2 tests, namely Pretest-Posttest. The data were processed using statistical analysis techniques. Hypothesis testing showed that there was a significant influence in this study from the data that had been tested, the data can be seen from the data analysis obtained the average results of the pretest (55.17) and posttest (87.76). Based on the results of this study, it can be concluded that the use of Question Cards has an effect on student learning outcomes in the fifth-grade science subject at the UPT SD Negeri 101906 Pagar Jati. This is also evidenced by the results of the data analysis test, which obtained a significance level of 0.000 < probability (0.05) and t = 3.104 > t = 1.01. Therefore, it is concluded that Ho is rejected and Ha is accepted, meaning "There is an Effect of Question Cards on Student Learning Outcomes in the fifth-grade science subject at the UPT SD Negeri 101906 Pagar Jati.